RNA Targeting by the Type III-A CRISPR-Cas Csm Complex of Thermus thermophilus - Staals, Raymond H. J. (Mol Cell, 2014)
CRISPR-Cas is a prokaryotic adaptive immune system that provides sequence-specific defense against foreign nucleic acids. Here we report the structure and function of the effector complex of the Type III-A CRISPR-Cas system of Thermus thermophilus: the Csm complex (TtCsm). TtCsm is composed of five different protein subunits (Csm1–Csm5) with an uneven stoichiometry and a single crRNA of variable size (35–53 nt). The TtCsm crRNA content is similar to the Type III-B Cmr complex, indicating that crRNAs are shared among different subtypes. A negative stain EM structure of the TtCsm complex exhibits the characteristic architecture of Type I and Type III CRISPR-associated ribonucleoprotein complexes. crRNA-protein crosslinking studies show extensive contacts between the Csm3 backbone and the bound crRNA. We show that, like TtCmr, TtCsm cleaves complementary target RNAs at multiple sites. Unlike Type I complexes, interference by TtCsm does not proceed via initial base pairing by a seed sequence.